Correlation of ultrasonography and fine needle aspiration cytology in diagnosis of hepatic space occupying lesions at Bankura Sammilani Medical College and Hospital - Poddar, Shubhankar; Ghosh, Apurba; Lalankumar, Jha Ashutoshkumar; China, Bibekananda (International Journal of Research in Medical Sciences, 2024)
Background: USG can differentiate various types of liver lesions based on their echo features and vascularity on CD then FNAC can be done only for those selected patients who needs further evaluation. Thus, patients with benign lesions based on USG and color Doppler, will be exempted from invasive, painful and time-consuming procedure of FNAC. Methods: It was an evaluation study of a diagnostic test and was cross sectional in design. Results: A total of 100 patients with focal hepatic lesions were included in our study group, with 47 cases diagnosed as abscesses, 2 cases were diagnosed as adenoma, 1 case was diagnosed as hepatic cyst, 1 case was diagnosed as cholangiocarcinoma, 22 cases were diagnosed as HCC and 21 cases were diagnosed as metastasis on FNAC. In diagnosis of abscess by USG, sensitivity was 87.23%, specificity was 93.33%, PPV was 93.18%, NPV was 87.5%, diagnostic accuracy was 90.21%. In diagnosis of HCC by USG, sensitivity was 63.64%, specificity was 84.28%, PPV was 56%, NPV was 88.05%, diagnostic accuracy was 79.34%. In diagnosis of metastasis by USG, sensitivity was 52.38%, specificity was 85.91%, PPV was 52.38, NPV was 85.91%, diagnostic accuracy was78.26%. Conclusions: Our study showed more than 75% diagnostic accuracy in diagnosing the commonest focal liver lesions like abscess, hepatocellular carcinoma and metastatic lesions, by USG as compared to FNAC diagnosis which was considered as confirmatory in our institution.